Detection of XSS Attacks in Web Applications: A Machine Learning Approach (International Journal of Innovative Research in Computer Science & Technology, 2021)
With the increased use of the internet, web  applications and websites are becoming more and more  common. With the increased use, cyber-attacks on web  applications and websites are also increasing. Of all the  different types of cyber-attacks on web applications and  websites, XSS (Cross-Site Scripting) attacks are one of the  most common forms of attack. XSS attacks are a major  problem in web security and ranked as number two web  application security risks in the OWASP (Open Web  Application Security Project) Top 10. Traditional methods  of defence against XSS attacks include hardware and  software-based web application firewalls, most of which are  rule and signature-based. Rule-based and signature-based  web application firewalls can be bypassed by obfuscating  the attack payloads. As such, rule-based and signature based web application firewalls are not effective against  detecting XSS attacks for payloads designed to bypass web  application firewalls. This paper aims to use machine  learning to detect XSS attacks using various ML (machine  learning) algorithms and to compare the performance of the  algorithms in detecting XSS attacks in web applications and  websites.
Keywords: Web Application; XSS Attacks; Machine Learning